Trends in surgical management and pre‐operative urodynamics in female medicare beneficiaries with mixed incontinence. Issue 2 (17th December 2015) - Chughtai, Bilal; Hauser, Nicholas; Anger, Jennifer; Asfaw, Tirsit; Laor, Leanna; Mao, Jialin; Lee, Richard; Te, Alexis; Kaplan, Steven; Sedrakyan, Art
Abstract : Objective: We sought to examine the surgical trends and utilization of treatment for mixed urinary incontinence among female Medicare beneficiaries. Methods: Data was obtained from a 5% national random sample of outpatient and carrier claims from 2000 to 2011. Included were female patients 65 and older, diagnosed with mixed urinary incontinence, who underwent surgical treatment identified by Current Procedural Terminology, Fourth Edition (CPT‐4) codes. Urodynamics (UDS) before initial and secondary procedure were also identified using CPT‐4 codes. Procedural trends and utilization of UDS were analyzed. Results: Utilization of UDS increased during the study period, from 38.4% to 74.0% prior to initial surgical intervention, and from 28.6% to 62.5% preceding re‐intervention. Sling surgery (63.0%) and injectable bulking agents (28.0%) were the most common surgical treatments adopted, followed by sacral nerve stimulation (SNS) (4.8%) and Burch (4.0%) procedures. Re‐intervention was performed in 4.0% of patients initially treated with sling procedures and 21.3% of patients treated with bulking agents, the majority of whom (51.7% and 76.3%, respectively) underwent injection of a bulking agent. Risk of re‐intervention was not different among those who did or did not receive urodynamic tests prior to the initial procedure (8.5% vs. 9.3%) Conclusions: Sling and bulk agents are the most common treatment for MUI. Preoperative urodynamic testing was not related to risk of re‐intervention following surgery for mixed urinary incontinence in this cohort. Neurourol. Urodynam. 36:422–425, 2017 . © 2015 Wiley Periodicals, Inc.